The Influence Of Motivation , Competence , Discipline and Compensation for Employee Performance PT HENIDA JAYA Group - Elva Lestari; Meita Pragiwani; M Benny Alexandri (BPJP - STEI, 2020)
motivation , competence , discipline and compensation on the performance of an employee of pt .Tektonindo henida jaya group .The research is quantitative methods using data primary and secondary data .The research is the total sample as many as 128 people .Data processing in this study used a spss analysis , and the analysis using multiple linear regression analysis .The analysis used in this research include the validity , reliability test , a determination , multiple linear regression , test research findings indicate that , 1 ( ) motivation no significant impact on employee performance , 2 ( ) competence significant impact on employee performance , 3 ( ) discipline significant impact on employee performance , 4 ( ) compensation significant impact on employee performance .